Financial Soundness Indicators-Experience with the Coordinated Compilation Exercise and Next Steps-Background Paper. (Policy Papers; Policy Paper, 2007)
This is the companion background paper to the staff report on Financial Soundness Indicators (FSIs): Experience with the Coordinated Compilation Exercise and Next Steps. It provides detailed information on the modalities of the Coordinated Compilation Exercise (CCE), the experience with the CCE, the issues that arose in that exercise regarding the compilation methodology in the Financial Soundness Indicators: Compilation Guide (Guide), and the matters that were taken into account in considering the specific amendments to the Guide, presented in the staff report.